(untitled) (Rajarshi Janak University Research Journal, 2024)
Bhisham Sahni’s adapted myth, in the form of a drama, portrays the character Madhavi as a victim of patriarchy. She is used to fulfil the male ego, such as Galav’s stubbornness for Gurudakshina, Yayati’s generosity, and Vishwamitra’s sexual desire. However, in the end, she valiantly challenges the male domination by boycotting the Swayambar. It deals with the issue of micro resistance from the characters belonging to the margin. Furthermore, it endeavours to reveal the process of modernity through resistance, the practice of self-decision, and the use of reason, which serves the purpose of elevating modern human beings from the docile to the autonomous agency, resulting in a modern social context. This study aims to reveal the hitherto cultural hegemony prevalent in society through the use of myth and creating the spirit of modernity. The text, Madhavi, in English, was selected purposefully for data collection and analysis. Data related to the resisters, authorities resisted, causes, and the way of resistance were collected and coded, determining the categories to develop the broad theme of resistance from the margin. Themes were analyzed, making connections among the categories and approaching with the theories of modernity, especially accentuating traits of the modern person. The findings indicate that characters from the margin, such as Ashramites, Tapas, and Madhavi, challenge the authorities from educational, cultural, and political domains. They resist the authorities for justice and social harmony through rationality. The revelations suggest that an in-depth study of mythical episodes can further reveal more about the malpractices and beliefs prevalent in society, which can pave the way for the search for modernity.